Hypnobreastfeeding: A Therapy to Reduce Anxiety and Enhance Breastfeeding Self-Efficacy - Asih, Yusari; Purwaningsih, Dewi; Sudarmi, Sudarmi (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Background: Maternal anxiety is a psychological factor that can interfere with the breastfeeding process, while breastfeeding self-efficacy—defined as a mother's confidence in her ability to breastfeed—is a strong predictor of exclusive breastfeeding success. Hypnobreastfeeding is a therapy that combines relaxation techniques and positive suggestions to help reduce anxiety and enhance self-efficacy. Purpose: This study aimed to evaluate the effectiveness of hypnobreastfeeding therapy in reducing anxiety levels and increasing breastfeeding self-efficacy among postpartum mothers. Methods: A quasi-experimental study with a pre-test–post-test control group design was conducted involving 60 postpartum mothers selected using purposive sampling (30 in the intervention group, 30 in the control group). The intervention consisted of four hypnobreastfeeding sessions delivered over a two-week period. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS), and breastfeeding self-efficacy was assessed with the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF). Data were analyzed using paired t-tests and independent t-tests to compare pre- and post-intervention scores. Results: The intervention group showed a statistically significant reduction in anxiety levels (p < 0.001) and a significant increase in breastfeeding self-efficacy scores (p < 0.001) compared to the control group. Conclusion: Hypnobreastfeeding is an effective intervention for reducing maternal anxiety and improving breastfeeding self-efficacy. It is recommended as a supportive approach in breastfeeding education and maternal mental health programs in clinical and community health settings.